EFEKTIVITAS GRANUL DAUN SALAM (Eugenia polyantha Wight) SEBAGAI LARVASIDA NYAMUK Aedes aegypti - Priadi Eling Waskito; Widya Hary Cahyati (Balai Penelitian dan Pengembangan Kesehatan Baturaja, 2018)
The usage of synthetic larvicide has many weakness, such as causing resistance. The alternative way to reduce the unwanted impact by using biolarvicide from plants such as the bay leaf (Eugenia polyantha Wight). The purpose of this research is to find out the larvicidal effect of bay leaf extract granule againts Aedes aegypti. The study was conducted with true experiment method with post test only control group design. The population of this research was Ae. aegypti larvae instar III in IVRCRD Salatiga. Total sample were 600 larvae used. The data was analyzed with univariate and bivariate analysis (Kruskal Wallis) by using SPSS. The result showed that there was correlation between bay leaf extract granule due to larvae mortality (p=0.001). The value of LC50 of bay leaf extract granule is 3,646.770 mg and LC90 is 9,430.171 mg. The value of LT50 of 3,500 mg is 27.462 hours, while LT90 is 4.778E3 hours. Based on acute toxicity test, it has affected to Ae. aegypti larvae.